From school to university: staff perspectives on supporting student inclusion and wellbeing - Pinto, Arnfrid Farbu; Mjøen, Odd Morten; Reed, Nina Petersen (Frontiers in Education, 2025)
This study explores how university staff perceive students’ needs in the transition from school to higher education, and how they reflect on their own role in promoting students’ wellbeing. We conducted five focus group interviews with 27 staff members across five university campuses. The material was analyzed using reflexive thematic analysis to identify shared reflections on transitions and support for student wellbeing. Our findings show that staff perceive students’ expectations to be shaped by their prior schooling, particularly the structured and closely guided environment of high school. This may generate some challenges for students when integrating into the more autonomous learning culture at university. University staff perceive that students’ needs and expectations have changed over time, alongside increased student diversity and a widened gap between resourceful and vulnerable students. They discussed how these developments bring about both academic and social challenges for students and university staff, requiring greater efforts to support student wellbeing, inclusion and academic achievement. Further, they highlighted the difficulty and tension of balancing tailored support with the need to uphold academic standards. Drawing on these findings, we discuss how university staff respond to shifting student expectations, how institutional frameworks shape everyday practice, and whether current university models adequately support inclusive and sustainable student wellbeing.